2016
DOI: 10.4315/0362-028x.jfp-16-124
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration and Identification of Coliform Bacteria Injured by Chlorine or Fungicide Mixed with Agricultural Water

Abstract: Chemical sanitizers may induce no injury (bacteria survive), sublethal injury (bacteria are injured), or lethal injury (bacteria die). The proportion of coliform bacteria that were injured sublethally by chlorine and fungicide mixed with agricultural water (pond water), which was used to dilute the pesticide solution, was evaluated using the thin agar layer (TAL) method. In pure cultures of Enterobacter cloacae , Escherichia coli , and E. coli O157:H7 (representing a human pathogen), the percentage of chlorine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The percentage of the injured population was 45 to 97% for thiophanate-methyl-treated cells, 80 to 87% for procymidone-treated cells, and 50 to 97% for ethylene oxide-treated cells. These results demonstrate the importance of choosing not only the right sanitizer but also the right sanitizer concentrations so that the treatment kills target microorganisms completely rather than just injures the cells (58).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The percentage of the injured population was 45 to 97% for thiophanate-methyl-treated cells, 80 to 87% for procymidone-treated cells, and 50 to 97% for ethylene oxide-treated cells. These results demonstrate the importance of choosing not only the right sanitizer but also the right sanitizer concentrations so that the treatment kills target microorganisms completely rather than just injures the cells (58).…”
Section: Discussionmentioning
confidence: 83%
“…However, limited information is available in the literature about the conditions under which sublethally injured cells are formed and the characteristics of these sublethally injured cells. In a study conducted by Izumi et al (58), the proportion of chlorine-injured Enterobacter cloacae, E. coli, and E. coli O157:H7 cells in pure culture was shown to be between 69 and 77%. Fungicides, including thiophanate-methyl (Topsin-M), procymidone (Sumilex), and ethylene oxide (Oxirane), also caused the formation of injured cells.…”
Section: Discussionmentioning
confidence: 98%
“…In another study, Hou et al (2017) found that drug-resistant bacteria accounted for 51.72% among 58 injured non-fastidious bacteria isolated from drinking water, and 80% of them had obvious multi-drug resistance. Besides, Izumi et al (2016) showed that chlorine-injured bacterial cells accounted for 69-77% in diluted electrolyzed water containing 2 mg/L available chlorine. When agricultural water was mixed with electrolyzed water, the injury rate of coliforms was about 75%, and the bactericidal products diluted to the recommended concentration could also cause injury to the coliforms in agricultural water.…”
Section: Existence and Threat Of Disinfectant-injured Bacteriamentioning
confidence: 99%
“…Since we previously reported that electrolyzed water containing chlorine caused chlorine-injury to a pure culture of E. coli Izumi et al, 2016a , E coli O157:H7 was injured sublethally by using electrolyzed water. Electrolyzed strongly acidic water pH 2.7, 25 ppm available chlorine was generated using a water electrolyzer -Light Amano, Yokohama, Japan , and then diluted to the concentration of 0.5, 1, 2, 3, and 4 ppm of available chlorine with sterile distilled water.…”
Section: Cell Suspension and Chlorine Treatmentmentioning
confidence: 99%